2022
DOI: 10.1177/0958305x221106618
|View full text |Cite
|
Sign up to set email alerts
|

Impact and performance efficiency analysis of grid-tied solar photovoltaic system based on installation site environmental factors

Abstract: The performance of solar photovoltaic systems tends to decline if the operating conditions change from the nominal operating cell temperature due to environmental factors. The major factors include temperature and humidity variations, which cause thermal losses and open-circuit voltage drops in photovoltaic panels. This study investigates the correlations between solar photovoltaic performance and environmental factors by quantifying the real-time variables including temperature, humidity, dewpoint temperature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Based on the reviewed literature, it is evident that existing studies on PV cell performance primarily focus on assessing the feasibility of specific locations for solar energy harnessing, determining the optimal tilt angle for maximum output, , comparing the performance of different PV cell technologies, , and investigating the effects of various meteorological parameters on PV cell performance. The meteorological parameters considered include solar intensity, , ambient temperature, humidity, wind speed, ,, and dew point . However, among these studies, only Bhattacharya et al developed a correlation to predict PV module efficiency using meteorological data such as temperature, humidity, and solar radiation.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Based on the reviewed literature, it is evident that existing studies on PV cell performance primarily focus on assessing the feasibility of specific locations for solar energy harnessing, determining the optimal tilt angle for maximum output, , comparing the performance of different PV cell technologies, , and investigating the effects of various meteorological parameters on PV cell performance. The meteorological parameters considered include solar intensity, , ambient temperature, humidity, wind speed, ,, and dew point . However, among these studies, only Bhattacharya et al developed a correlation to predict PV module efficiency using meteorological data such as temperature, humidity, and solar radiation.…”
Section: Introductionmentioning
confidence: 99%
“…They also observed that El Jadida, despite having a lower solar intensity than BeniMellal, had a higher production capacity, indicating the significant influence of meteorological parameters on PV cell productivity. Iqbal et al 26 investigated the power loss caused by temperature, humidity, dew point, and heat index at three different locations: rooftop, parking area, and ground level. They reported that the highest power loss occurred at the ground level, followed by the rooftop and parking areas in sequential order.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The efficiency of commercial PV cells is rated between 10 and 20% with $0.1-0.24/kwh (Photovoltaic Energy Factsheet, 2021) (Soomar et al, 2022) while the remaining incident solar energy is mostly wasted as heat, which further reduces their overall efficiency by decreasing the voltage generated. In addition, there are shading losses in a solar panel when every cell in the panel has to operate at the reduced current set by shaded cells which may be remedied by installing panels on the roof or in open lots (Iqbal et al, 2022). Alternatively, there are ways to increase overall energy yield of solar panels.…”
Section: Introductionmentioning
confidence: 99%